Single-cell analyses highlight the proinflammatory contribution of C1q-high monocytes to Behçet’s disease - Zheng, Wenjie; Wang, Xiaoman; Liu, Jinjing; Yu, Xin; Li, Lu; Wang, Heping; Yu, Jijun; Pei, Xiaoya; Li, Chaoran; Wang, Zhimian; Zhang, Menghao; Zeng, Xiaofeng; et al. (Proceedings of the National Academy of Sciences - PNAS, 2022)
Behçet’s disease (BD) is a chronic vasculitis characterized by systemic immune aberrations. However, a comprehensive understanding of immune disturbances in BD and how they contribute to BD pathogenesis is lacking. Here, we performed single-cell and bulk RNA sequencing to profile peripheral blood mononuclear cells (PBMCs) and isolated monocytes from BD patients and healthy donors. We observed prominent expansion and transcriptional changes in monocytes in PBMCs from BD patients. Deciphering the monocyte heterogeneity revealed the accumulation of C1q-high (C1qhi) monocytes in BD. Pseudotime inference indicated that BD monocytes markedly shifted their differentiation toward inflammation-accompanied and C1qhi monocyte–ended trajectory. Further experiments showed that C1qhi monocytes enhanced phagocytosis and proinflammatory cytokine secretion, and multiplatform analyses revealed the significant clinical relevance of this subtype. Mechanistically, C1qhi monocytes were induced by activated interferon-γ (IFN-γ) signaling in BD patients and were decreased by tofacitinib treatment. Our study illustrates the BD immune landscape and the unrecognized contribution of C1qhi monocytes to BD hyperinflammation, showing their potential as therapeutic targets and clinical assessment indexes.